Early age thermal cracking resistance of basalt fiber-reinforced concrete for mass concrete structures under restraint condition. (November 2022) - Xin, Jianda; Jiang, Xiaoming; Chen, Zhongyong; Zuo, Leigao; Zhang, Guoxin; Wang, Zhenhong; Qi, Chunyu; Zhang, Lei; Liu, Yi
Abstract: This study investigated the early-age thermal cracking behavior of basalt fiber (BF)-reinforced concrete exposed to rapid temperature changes (0.5 °C/h) at different curing ages of 3, 7, and 14 d, at fiber volume dosages of 0 %, 0.1 %, and 0.5 % using a developed temperature stress testing machine (TSTM). The material properties testing results demonstrated that as the BF dosage increased from 0 % to 0.1 %, and 0.5 %, the greatest reductions in the elastic modulus of BF-reinforced concrete relative to ordinary concrete were 18.9 % and 8.3 %, respectively, and the greatest increases in the axial tensile strength were 5.6 % and 13.5 %, respectively. The thermal stress test results indicated that the thermal cracking risk (cracking temperature difference) of BF-reinforced concrete vary nonlinearly with the increasing basalt fiber dosage. As the BF dosage increased from 0 % to 0.1 % and 0.5 %, the maximum increases in the temperature drop were 42.9 % and 18.3 %, respectively. Additionally, the stress relaxation of concrete subjected to a rapid temperature change appeared gradually after 9 h loading, and the concrete with a fiber dosage of 0.1 % showed the greatest degree of relaxation (i.e., 0.216), which was greater than that of reference concrete by 42.1 %. In regard to the thermal cracking resistance, the optimal BF dosage obtained in the current research was 0.1 % (vol.). The relationship established between the cracking temperature differences and BF dosages can help engineers to effectively assess the risk of surface temperature cracking in harsh environments during the construction period of mass concrete structure.